2019
DOI: 10.1186/s13006-019-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding by South African mothers living with HIV: implications for future training of health care workers and the need for consistent counseling

Abstract: Background Since 2010, the World Health Organization recommends lifelong antiretroviral treatment for all women living with HIV, and exclusive breastfeeding for six-months followed by breastfeeding until 24-months for all HIV positive mothers. Nevertheless, many mothers living with HIV do not initiate breastfeeding or stop prematurely, and many countries are still in the process of updating their national infant feeding guidelines to align with World Health Organization recommendations. We sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 15 publications
2
73
0
Order By: Relevance
“…Individual questions Overall exclusive breastfeeding uptake in our study was similar to other studies from South Africa and elsewhere [19,20,23,25,29]. Our study mirrors two other studies on differences in exclusive breastfeeding uptake among women living with HIV compared with women not living with HIV in the Option B+ era [19,20], despite being nested within a trial specifically targeting antenatal care quality for all women.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Individual questions Overall exclusive breastfeeding uptake in our study was similar to other studies from South Africa and elsewhere [19,20,23,25,29]. Our study mirrors two other studies on differences in exclusive breastfeeding uptake among women living with HIV compared with women not living with HIV in the Option B+ era [19,20], despite being nested within a trial specifically targeting antenatal care quality for all women.…”
Section: Discussionsupporting
confidence: 86%
“…Median age was 25 years (interquartile range [IQR], [21][22][23][24][25][26][27][28][29][30]. Median gestation at first ANC visit was 19 weeks (IQR 15-24 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such echoes from previous national guidelines need to be managed in the retraining of health care providers to avoid a detrimental impact on child health. A recent qualitative study undertaken in Johannesburg (West et al, ) also found that mothers living with HIV expressed confusion around continued breastfeeding after the introduction of complementary foods. This confusion was pervasive among both mothers and health care providers.…”
Section: Discussionmentioning
confidence: 97%
“…This remains a considerable challenge; research from several settings has documented confusion among health workers on how to advise and support women to breastfeed, due to incomplete training coverage and weak supervision (Chinkonde, Sundby, de Paoli, & Thorsen, ; Chopra, Doherty, Jackson, & Ashworth, ; Janse van Rensburg, Nel, & Walsh, ; Piwoz et al, ). In addition, attitudes and fear among health workers have also contributed to inappropriate infant feeding messages and reluctance to promote breastfeeding, particularly sustained breastfeeding, among mothers living with HIV mothers due to the role breastfeeding has in post‐natal HIV transmission (West et al, ).…”
Section: Introductionmentioning
confidence: 99%